The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3846/btp.2021.12330
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Wellbeing and Organizational Creativity: Personality Traits Role

Abstract: Organizational creativity is indispensable in a highly competitive and dynamic academic environment; and the role of individuals is mostly unquantifiable. Hence the study argued that the ideas, novel research output, patents, grants of the academic staff depend on the flexible wellbeing of the workforce which is at a low level in Nigeria. Thus, the paper investigated the role of personality traits on the relationship between flexible wellbeing and organizational creativity. The paper implemented a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Several previous studies have shown that personality is related to mental health [12][13][14][15] and psychological well-being [16]. In general, it is explained that an individual's character is one of the determinants of their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that personality is related to mental health [12][13][14][15] and psychological well-being [16]. In general, it is explained that an individual's character is one of the determinants of their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the novel efforts that provides empirical support to show a positive relationship between psychological, malleable and trainable attributes with employee creativity. This study also helps to address several gaps, including the need to identify individual characteristics (Korzynski et al ., 2020; Oldham and Cummings, 1996; Umukoro et al ., 2021) and psychological processes (Cai et al ., 2018; Choi, 2011; Yu et al ., 2019)that influence the creativity of employees in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Both the antecedents are malleable and may be improved with appropriate interventions by internal human resource (HR) professionals and line managers. This study also helps to address the need for research on individual characteristics (Korzynski et al ., 2020; Oldham and Cummings, 1996; Umukoro et al ., 2021)and psychological processes (Cai et al ., 2018) that influence the creativity of employees in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Sejalan dengan ini, beberapa studi tentang kepribadian menunjukkan keterkaitan dengan kesehatan mental (Bedaso & Han, 2021;Brailovskaia & Margraf, 2018;Bucher et al, 2019;Zhang et al, 2018) dan kesejahteraan psikologis (Umukoro et al, 2021). Penelitian lain juga menunjukkan kebribadian, seperti ekstraversi, agreeableness, openness to experience, consenciousness, neoritisme, dan honesty-humality memiliki hubungan dengan flourishing (Daigle et al, 2022;HalilEkşi İbrahimAlbayrak, FüsunEkşi, 2022;MacIntyre et al, 2019;Umucu et al, 2018).…”
Section: Pembahasanunclassified